A simple user-made iontophoresis device for palmoplantar hyperhidrosis - Rahul Nagar (Journal of Cutaneous and Aesthetic Surgery, 2016)
Iontophoresis is defined as passing of an ionized substance through intact skin by application of direct electric current. Tap water iontophoresis is reliable and effective method for treatment of palmar and plantar hyperhydrosis when practiced with appropriate technique and timing.One of the major setback for using iontophoresis is that the apparatus is expensive and is not readily available.A simple user-made Iontophoresis device have been described here, which could be easily constructed and used at home.